From public agency to hybrid organization: the institutional transformation of Cimahi Techno Park, Indonesia - Siti Widharetno Mursalim; Anry Firmansyah; Zulfikar Hanafi (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
This study analyzes the institutional dynamics of Cimahi Techno Park (CTP), a local government-owned Science and Technology Park (STP) currently undergoing a transformation toward a hybrid organizational model. The study aims to identify these gaps by analyzing institutional dynamics, characteristics of hybridity, and barriers to CTP’s transformation.  The research method employed is based on a qualitative case study, in which data were collected through interviews, observations, and document analysis to examine competing public-private logics, collaborative governance practices, and institutional barriers. The findings showed that although the CTP has developed early forms of hybridity through collaborative networks involving the government, academics, industry, and the creative community, its operational autonomy remains constrained by structural rigidity, limited financial autonomy, and gaps in human resource capacity. This study demonstrates that transforming the CTP from a public agency into STP a hybrid organization requires more than just administrative reforms; it necessitates broader institutional changes in governance, capacity, and policy alignment. The research has formulated a transformation model toward a Regional Public Service Agency that emphasizes human resource development, financial autonomy, and the institutionalization of collaborative governance mechanisms. This study contributes to the development of the concept of hybrid organizations as a public sector innovation in developing countries.